2023
DOI: 10.3389/fpsyg.2023.1074972
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic interventions impact brain function and promote post-traumatic growth in adults living with post-traumatic stress disorder: A systematic review and meta-analysis of functional magnetic resonance imaging studies

Abstract: IntroductionThe present systematic review and meta-analysis explores the impacts of cognitive processing therapy (CPT), eye movement desensitization and reprocessing (EMDR), and prolonged exposure (PE) therapy on neural activity underlying the phenomenon of post-traumatic growth for adult trauma survivors.MethodsWe utilized the following databases to conduct our systematic search: Boston College Libraries, PubMed, MEDLINE, and PsycINFO. Our initial search yielded 834 studies for initial screening. We implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 123 publications
0
1
0
Order By: Relevance
“…After its initial discovery other sensory domains such as sound and touch have been added (Shapiro, 1999). The technique is widely used, especially to treat the persistent stress associated with traumatic events (e.g., PTSD), but its neurological basis is not understood (Pierce et al, 2023;Valiente-Gomez et al, 2017;Zarghi et al, 2013). The success of the technique has been suggested to be due in part to the strong bilateral nature of the visual stimuli used and some authors have noted its relationship to the REM phase of sleep (Stickgold, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…After its initial discovery other sensory domains such as sound and touch have been added (Shapiro, 1999). The technique is widely used, especially to treat the persistent stress associated with traumatic events (e.g., PTSD), but its neurological basis is not understood (Pierce et al, 2023;Valiente-Gomez et al, 2017;Zarghi et al, 2013). The success of the technique has been suggested to be due in part to the strong bilateral nature of the visual stimuli used and some authors have noted its relationship to the REM phase of sleep (Stickgold, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…With recent research into complex PTSD, it has been observed how these impacts can occur in reverse as well; namely, that single events can produce complex PTSD, and individuals who experience chronic exposure can produce PTSD (Cloitre, 2020). While some research has been conducted into the neural substrates implicated in resilience and post-traumatic growth (Pierce et al, 2023), more work is needed to understand how environmental impacts of trauma lead to different mental health challenges.…”
Section: Strengths and Shortcomings Of Piementioning
confidence: 99%
“…Unfortunately, this trigger caused Michael to experience an episode of dissociation, where he was perceptually transported to the day of his close friend's tragic passing. Then, Michael's limbic system activates and causes his body to tense up, produce sweat, and experience harrowing feelings of panic (Pierce & Black, 2023a, 2023bPierce et al, 2023;Sherin, 2011).…”
Section: Causes and Effects For Core Conceptsmentioning
confidence: 99%
See 2 more Smart Citations